34‐2: A Rapid, Highly Emissive Procedure Synthesize of Giant Pure Red Coreshell Quantum Rods by Using Modified Tributylphosphine‐assisted Method. Issue 1 (May 2016) - Qin, Jing; Hao, Junjie; Chen, Wei; Deng, Jian; Wang, Dan; Xu, Bing; Wu, Dan; Wang, Kai; Li, Shang; Wen, Zuoliang
Abstract : We report pure red core‐shell CdSe/CdS quantum rods synthesized when the purified wurtzite CdSe core is activated by tributylphosphine‐assisted method. Satisfactory results showed that the spectrally narrow emission (27 nm), large stokes‐shift more than 165 and high quantum yield photoluminescence (>75%), represent color‐saturated red emission ideal for display applications.